2010
DOI: 10.1093/rheumatology/keq333
|View full text |Cite
|
Sign up to set email alerts
|

Patients with shoulder complaints in general practice: consumption of medical care

Abstract: Nearly half of patients with a new shoulder complaint consult their GP only once. Medical consumption in general practice is highest for male shoulder patients and the 45- to 64-year age group. Shoulder problems are mainly an issue for primary care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
23
2
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 15 publications
0
23
2
2
Order By: Relevance
“…16,41 Many measurement instruments have been developed to evaluate the problems that patients with shoulder complaints experience in their everyday functioning. 1,44 Shoulder-specific disability questionnaires, like the Disabilities of the Arm, Shoulder and Hand questionnaire (DASH) 1,27,34,44,56 and the Shoulder Pain and Disability Index (SPADI), 1,3,14,31,43,44 consist of a standard set of questions concerning activities that patients with shoulder pain, in general, experience difficulty with.…”
mentioning
confidence: 99%
“…16,41 Many measurement instruments have been developed to evaluate the problems that patients with shoulder complaints experience in their everyday functioning. 1,44 Shoulder-specific disability questionnaires, like the Disabilities of the Arm, Shoulder and Hand questionnaire (DASH) 1,27,34,44,56 and the Shoulder Pain and Disability Index (SPADI), 1,3,14,31,43,44 consist of a standard set of questions concerning activities that patients with shoulder pain, in general, experience difficulty with.…”
mentioning
confidence: 99%
“…The rate of referrals to an orthopaedic surgeon or specialist in rehabilitation medicine in our material was higher (20%) than reported in the literature on new episodes of shoulder problems (5-14%). Surgery was also required more often (8% versus 0.38-2% in the literature) [3,7,10,19]. …”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that general practitioners seldom make a specific diagnosis for shoulder disorder, and that even a general diagnostic category has been shown to change over time in a significant proportion of individuals [7,13,23,24]. Diagnosis based on clinical examination performed even by an especially trained physician is frequently unreliable [13,23].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations